A Study on The Disease Pattern and Outcome in Neonatal Intensive Care Unit, Tertiary Care Hospital of Andhra Pradesh - Krishnaiah, Murali; Basha, Md Sajid; Khaleef, Abdul; Rahman, Zia Ur (Journal of Maternal and Child Health, 2023)
Background: There was very scanty data available regarding the neonatal morbidity and mortality patterns in NICU. Hence, the current study aimed to document and analyze the disease pattern, and outcome in neonates admitted in NICU of tertiary care center. Subjects and Method: A prospective observational study was conducted at neonatal intensive care unit (NICU) of SVRRGGH, Tirupati from September 2014 to August 2015. A total of 2287 newborns were admitted who met selection criteria. All neonate’s demographics, clinical profile, and outcome were analyzed. Results: From a total of 2287 newborns, 71.7% were delivered vaginally, 56.05% were male, 38.0% were <2500 g, and 48.02% were preterm babies. The neonatal deaths consisted of 448 (19.58%) newborns; 71.98% of whom pre-term babies, 80.8% of whom birth weight >2.5kg, 23.2% of whom out born, and majority died before 7 days of age. Neonatal sepsis (30.65%) is the most common cause of death followed by birth asphyxia hypoxic ischemic encephalopathy in 29.04%, hyaline membrane disease (11.03%), neonatal jaundice (9.68%), meconium aspiration syndrome (7.69%), hemorrhagic disease of newborn (1.68%), and congenital malformations (2.79%). There was a statistical association observed between neonatal death and gender (p= 0.023); neonatal death and mode of admission; neonatal death and gestational age (p <0.001); neonatal death and birth Weight (p< 0.001). Conclusion: current study identified preterm, low birth weight, neonatal sepsis, birth asphyxia, Hyaline membrane disease as major causes of morbidity and Neonatal sepsis, Hyaline Membrane Disease, and HIE as the major contributors to the neonatal mortality. Improving antenatal care, maternal health checkup and timely referral of high risk cases to tertiary care centers may help to improve neonatal outcome. Keywords: neonatal sepsis, antenatal care, low birth weight, neonatal mortality. Correspondence: Department of Pediatrics, Government general hospital, Rajiv Gandhi Institute of Medical Sciences, Kadapa, Andhra Pradesh-516002, India